1985
DOI: 10.1002/j.1551-8833.1985.tb05508.x
|View full text |Cite
|
Sign up to set email alerts
|

Removing Color Caused by Humic Acids

Abstract: Optimum domains for the removal of color during the coagulation process were studied in a series of jar tests and diagrammed as an aid to the design and operation of water treatment plants. The mechanisms for the removal of color associated with humic acids seem to be closely related to those associated with the removal of turbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
10

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 8 publications
4
39
0
10
Order By: Relevance
“…An analysis of Figures 2-5 reveals two regions in which coagulation with Fenton's reagent and subsequent fl occulation and fl otation produce removal effi ciencies greater than or equal to 50% and 60% for the fi rst (lower pH) and second (higher pH) region, respectively. Similar behaviour was observed by Edwards and Amirtharajah (1985), who also worked with water sample with true colour of 100 HU (caused by the addition of humic acid) and turbidity equal to zero, using aluminium sulphate (alum) as a coagulant. These researchers concluded that in the fi rst region, corresponding to approximate coagulation pH values of 3.6 to 4.6 in the current study (Figures 2-5), the hydrolysing species adsorption mechanism was probably dominant, causing charge neutralisation of HS molecules.…”
Section: Coagulation Diagramssupporting
confidence: 72%
See 1 more Smart Citation
“…An analysis of Figures 2-5 reveals two regions in which coagulation with Fenton's reagent and subsequent fl occulation and fl otation produce removal effi ciencies greater than or equal to 50% and 60% for the fi rst (lower pH) and second (higher pH) region, respectively. Similar behaviour was observed by Edwards and Amirtharajah (1985), who also worked with water sample with true colour of 100 HU (caused by the addition of humic acid) and turbidity equal to zero, using aluminium sulphate (alum) as a coagulant. These researchers concluded that in the fi rst region, corresponding to approximate coagulation pH values of 3.6 to 4.6 in the current study (Figures 2-5), the hydrolysing species adsorption mechanism was probably dominant, causing charge neutralisation of HS molecules.…”
Section: Coagulation Diagramssupporting
confidence: 72%
“…Furthermore, coagulant dosages (Fenton) were lower in the fi rst region than for the second region. As observed by Edwards and Amirtharajah (1985), it seems to have a restabilisation region between the two regions in which the coagulation resulted effi cient.…”
Section: Coagulation Diagramsmentioning
confidence: 75%
“…La nature ainsi que la concentration des matières organiques doivent également être prises en compte (VIK et ai, 1985) et l'on peut noter comme pour l'effet de la temperature, que l'ajout de matières minérales permet d'améliorer le rendement d'élimination des substances organiques (EDWARD et AMIRTHARAJAH, 1985). HUNDT et O'MELIA (1988) Les essais de floculation ont été réalisés sur jar-test Hydrocure FLH6.…”
Section: Pour Pallier Ces Inconvénients Le Service Des Eaux De La VIunclassified
“…Une simulitude apparaît ici, avec les travaux d 'EDWARD et AMIRTHARAJAH (1985) dont il ressort que le rendement d'élimination des colloïdes organiques peut être amélioré par un ajout de matières minérales.…”
Section: Residue Curves (Expérimental Dose -Calculated Dose) Versus Cunclassified
“…Charge neutralization/complexation is believed to preferentially occur at acidic pH [9][10][11], while physical enmeshment and/or adsorption commonly occurs under conditions favoring metal hydroxide precipitation, and humic substances are primarily transferred onto freshly formed precipitate [9,10,12,13]. When FeCl 3 is employed in enhanced coagulation for HA removal, good performance has been gained at acidic pH and large doses, where in pH-coagulant concentration domains fresh iron hydroxide precipitation is formed [4][5][6].…”
Section: Introductionmentioning
confidence: 99%